Body mass index and fitness in high-functioning children and adolescents with cerebral palsy: What happened over a decade?. (December 2017) - Zwinkels, Maremka; Takken, Tim; Ruyten, Thijs; Visser-Meily, Anne; Verschuren, Olaf; ,
Highlights: Performance-related fitness in children and adolescents with CP was better for the 2014 cohort as compared to the 2004 cohort. VO2 peak values did not change over 10 years. Currently available reference values might underestimate performance-related fitness of children and adolescents with CP today. Body mass and BMI were substantially higher for the 2014 cohort; combination of gained muscle- and fat mass? Abstract: Background: In recent decades, improving fitness has become an important goal in rehabilitation medicine in children and adolescents with cerebral palsy (CP). Aims: To compare body mass index (BMI), performance-related fitness, and cardiorespiratory fitness of children with CP measured in 2014 with a comparable sample from 2004. Methods and procedures: In total, 25 high-functioning children with CP (i.e., GMFCS I–II) measured in 2004 (13 boys; mean age 13.2 (2.6) years) were matched to 25 children measured in 2014. Outcomes included body mass and BMI, muscle power sprint test (MPST), 10 × 5 m sprint test, and a shuttle run test (SRT). Data of 15 participants from 2004 (10 boys; mean age 12.6 (2.5) years) were matched and analysed for VO2 peak. Outcomes and results: Body mass and BMI were higher (both: p < 0.05) in the 2014 cohort compared to the 2004 cohort. Further, performance-related fitness was better for the 2014 cohort on the MPST ( p = 0.004), the 10 × 5 m sprint test ( p = 0.001), and the SRT ( p < 0.001). However, there were no differences for VO2 peak. Conclusions and implications: In high-funcitoning children with CP, there are positive ecological time trends in performance-related fitness, but not in VO2 peak between 2004 and 2014. The substantial higher body mass and BMI is alarming and requires further investigation.